2016
DOI: 10.1111/exd.12988
|View full text |Cite
|
Sign up to set email alerts
|

The crucial role of IL‐22 and its receptor in thymus and activation regulated chemokine production and T‐cell migration by house dust mite extract

Abstract: House dust mite (HDM) is known as one of the factors that causes atopic dermatitis (AD). Interleukin (IL)-22 and thymus and activation regulated chemokine (TARC) are related to skin inflammatory disease and highly expressed in AD lesions. However, the effects of HDM on IL-22 production in T cells and on TARC production and IL-22Rα receptor expression in keratinocytes are unknown. To identify the role of HDM in keratinocytes and T cells, we investigated IL-22Rα expression and TARC production in the human kerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…Intriguingly, the serum TARC level positively correlated with the serum IL‐22 level in GPP patients. Jang et al 25 . has reported that house dust mite extract‐induced IL‐22 from T cells significantly increased TARC production in the human keratinocyte cell line, HaCaT.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the serum TARC level positively correlated with the serum IL‐22 level in GPP patients. Jang et al 25 . has reported that house dust mite extract‐induced IL‐22 from T cells significantly increased TARC production in the human keratinocyte cell line, HaCaT.…”
Section: Discussionmentioning
confidence: 99%
“…IL-22 and IL-17 synergistically increase the levels of S100 proteins and AMPs in the epidermis [12,136]. IL-22 secretion can be induced immediately in response to staphylococcal exotoxins and house dust mites and can potentially amplify chronic skin inflammation in patients with AD [137,138]. IL-22 can also stimulate CCL17 production from human keratinocytes and promote the migration of T cells into the skin [138].…”
Section: Immunological Abnormalitiesmentioning
confidence: 99%
“…IL-22 secretion can be induced immediately in response to staphylococcal exotoxins and house dust mites and can potentially amplify chronic skin inflammation in patients with AD [137,138]. IL-22 can also stimulate CCL17 production from human keratinocytes and promote the migration of T cells into the skin [138]. Upregulated IL-22 in chronic AD induces matrix metalloproteinase-3, a marker of remodeling; stromelysin-1; platelet-derived growth factor A; and CXCL5 (chemokine, CXC motif, ligand 5) [139].…”
Section: Immunological Abnormalitiesmentioning
confidence: 99%
“…Recently, Th17 and Th22 cells have been implicated in AD-related immune dysregulation by amplifying the inflammatory response 11 . IL-17 and IL-22 are main effective cytokines of Th17 and Th22 cells, which could induce the secretion of IL-1β, TNF-α and other pro-inflammatory cytokines 12 , 13 . The functional IL-22 receptor consists of two receptor subunits, IL-22R1 and IL-10R2, among which IL-22R1 plays a much more important role than IL-10R2 during AD 13 .…”
Section: Resultsmentioning
confidence: 99%